PENGARUH KONSENTRASI BERBAGAI LARUTAN GULA SAKAROSA TERHADAP SUDUT PUTAR JENIS CAHAYA MERAH, HIJAU DAN KUNING - Mita Kusuma Purwasih (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Sugar is optically an active substance that has a ability to rotate the direction of vibration light passing through it. The aim of this research is to study the influence of concentrations of various sucrose solutions to the light polarization angle.                As a light source was used red laser pointer with wavelength of 650 nm, green laser pointer with wavelength of 532 nm, and yellow light source from halogen lamp projecteur with maximum power of 150 watt. The solution used including three kinds of sugar, there were Tropicana Slim, Gulaku sugar, and MK, with each concentration was 10%, 20%, 30%, 40% and 50%. The angle of polarization were varied from 0o, 30o, and 60o with each ot the angle is repeated as much as 10 times, then it was sought analisator angle corresponding to the minimum light intensity transmission. The data processing is done by the weighted average  techniques, and then made curve the relations between concentration of analisator angle to angle of polarization.                The result of the research indicate that concentration of sugar and wavelength influence the change of polarization angle. The higher the concentration of sugar the larger the angle of polarization. The changes of polarization angel from the biggest were Tropicana Slim, Gulaku and MK. While for the wavelength, the smaller of the wavelength the larger the changes of total polarization angle. The changes of polarization angel from the biggest were green laser, yellow light, and red laser.Key words: polarization, optical substance, wavelength, sugar solution